Signs of Socioeconomic Status - Kraus, Michael W.; Keltner, Dacher (Psychological Science, 2009)
Socioeconomic status (SES) is a primary determinant of health vulnerabilities and social affiliations. To ascertain if SES is signaled in brief patterns of nonverbal behavior, we had participants of varying SES backgrounds engage in a brief interaction with a stranger. Videos of 60-s slices of these interactions were coded for nonverbal cues of disengagement and engagement, and estimates of participants' SES were provided by naive observers who viewed these videos. As predicted by analyses of resource dependence and power, upper-SES participants displayed more disengagement cues (e.g., doodling) and fewer engagement cues (e.g., head nods, laughs) than did lower-SES participants. Results were also consistent with the thin-slicing literature, in that observers' estimates of SES were reliable with each other and accurately predicted targets' family income, maternal education, and subjective SES. Finally, nonverbal displays of disengagement and engagement predicted observers' estimates of SES, which suggests that these cues are systematic signs of SES. These results have implications for understanding the effect of SES on social interactions and patterns of disengagement and engagement in other realms.